Loading of dendritic cells for immunotherapy. (31st May 2013) - Van, A. M. T.; Benteyn, D.; Wilgenhof, S.; Corthals, J.; Heirman, C.; Neyns, B.; Bonehill, A.; Thielemans, K.
<x xml:space="preserve">Abstract</x> Dendritic cell therapy has been optimized a lot aiming to induce a strong and broad immune response in terms of the recognized epitopes by both CD8+ and CD4+ T cells and the use of the patients' complete unique set of HLA molecules. We here give an overview of our approach for antigen loading and maturation of dendritic cells and describe the consequences to evaluate the immune response after treatment as well as the Brussels experience in clinical trials.